The confirmatory factor structure of neurological soft signs in Nigerians with first episode schizophrenia (2015)
We describe empirically derived categories of NSS in first episode schizophrenia among indigenous Africans. A total of 84 Nigerian patients with the disease were assessed using the neurological evaluation scale. An exploratory factor analysis with orthogonal varimax rotation was first conducted and the factors derived based on a priori criteria were subjected to confirmatory analyses using SPSS 18.0 and AMOS 18.0. We tested four different competing models to identify the structure with the best fit to the data. The relationship of the derived NSS structure with the clinical characteristics of schizophrenia was then explored using the Pearson correlation method. The overall clinical status was assessed using the positive and negative syndrome scale and clinical global impression. Additional assessments included the pre-morbid adjustment scale and calgary depression scale for schizophrenia. A three factor structure in which stereognosis is prescribed to load into a ‘perceptual and motor sequencing’ category (audio–visual integration, fist-edge palm, rhythm tapping, extinction, right–left confusion) provided the best fit to the data (chi-square goodness of fit test = 1.25; comparative fit index = 0.95; root square means error of approximation < 0.001), and disorganization (r = 0.559, p < 0.001) psychopathologies. NSS in this sample are heterogeneous, but aggregates into three correlated categories with significant overlap with previously described classifications.